Reliability-based optimization of external wrapping of CFRP on reinforced concrete columns considering decayed diffusion. (October 2021) - Ayazian, Rouhollah; Abdolhosseini, Mohaddeseh; Firouzi, Afshin; Li, Chun-Qing
Highlights: Reliability-based optimization of CFRP-wrapped RC columns was conducted using GA and PSO. Decayed diffusion and time-dependent corrosion progress were modeled and reliability analysis was performed. The optimum CFRP strengthening strategy are determined in different diffusion scenarios. Abstract: A cost-efficient maintenance plan is crucial to ensure the reliability of decayed reinforced concrete (RC) structures. A reliability-based optimization strategy is proposed that considers a time-variant deterioration model for planning the optimal time and degree of carbon-based fiber reinforcement polymer (CFRP) strengthening of RC columns. A genetic algorithm (GA) has been used as an optimization tool, and the particle swarm optimization algorithm was used to validate the outcomes. A deteriorating RC column exposed to chloride attack was modeled to compare the time-dependent failure probabilities calculated by a recently-developed closed-form equation and the correspondent reliability indexes as lifetime performance indicators. The influence of CFRP wraps on the decayed diffusion rate, and corrosion current density has been modeled using existing formulations. The results of the decaying diffusion model also have been compared to the extreme cases of "no influence" and "complete corrosion stop". It was found that a GA can successfully determine the optimum solution in terms of the number of required CFRP layers and strengthening time to yield the minimum life-cycle costs. The findings can assist engineers and asset owners in providing optimized maintenance and repair strategies for decayed structures. It also highlights the significance of proper modeling of the corrosion process in CFRP-strengthened RC columns.